Nano-silver-incorporated biomimetic polydopamine coating on a thermoplastic polyurethane porous nanocomposite as an efficient antibacterial wound dressing - Menglong Liu; Tengfei Liu; Xiwei Chen; Jiacai Yang; Jun Deng; Weifeng He; Xiaorong Zhang; Qiang Lei; Xiaohong Hu; Gaoxing Luo; Jun Wu (Journal of Nanobiotechnology, 2018)
Abstract Background Developing an ideal wound dressing that meets the multiple demands of good biocompatibility, an appropriate porous structure, superior mechanical property and excellent antibacterial activity against drug-resistant bacteria is highly desirable for clinical wound care. Biocompatible thermoplastic polyurethane (TPU) membranes are promising candidates as a scaffold; however, their lack of a suitable porous structure and antibacterial activity has limited their application. Antibiotics are generally used for preventing bacterial infections, but the global emergence of drug-resistant bacteria continues to cause social concerns. Results Consequently, we prepared a flexible dressing based on a TPU membrane with a specific porous structure and then modified it with a biomimetic polydopamine coating to prepare in situ a nano-silver (NS)-based composite via a facile and eco-friendly approach. SEM images showed that the TPU/NS membranes were characterized by an ideal porous structure (pore size: ~ 85 μm, porosity: ~ 65%) that was decorated with nano-silver particles. ATR-FITR and XRD spectroscopy further confirmed the stepwise deposition of polydopamine and nano-silver. Water contact angle measurement indicated improved surface hydrophilicity after coating with polydopamine. Tensile testing demonstrated that the TPU/NS membranes had an acceptable mechanical strength and excellent flexibility. Subsequently, bacterial suspension assay, plate counting methods and Live/Dead staining assays demonstrated that the optimized TPU/NS2.5 membranes possessed excellent antibacterial activity against P. aeruginosa, E. coli, S. aureus and MRSA bacteria, while CCK8 testing, SEM observations and cell apoptosis assays demonstrated that they had no measurable cytotoxicity toward mammalian cells. Moreover, a steady and safe silver-releasing profile recorded by ICP-MS confirmed these results. Finally, by using a bacteria-infected (MRSA or P. aeruginosa) murine wound model, we found that TPU/NS2.5 membranes could prevent in vivo bacterial infections and promote wound healing via accelerating the re-epithelialization process, and these membranes had no obvious toxicity toward normal tissues. Conclusion Based on these results, the TPU/NS2.5 nanocomposite has great potential for the management of wounds, particularly for wounds caused by drug-resistant bacteria.